Continuous manufacturing of reentrant structures via roll‐to‐roll process. Issue 1 (23rd September 2018) - Kodihalli Shivaprakash, Nischay; Zhang, Jinde; Panwar, Artee; Barry, Carol; Truong, Quoc; Mead, Joey
ABSTRACT: Reentrant structures have been deemed necessary for repelling low‐surface‐tension liquids. In this article, a novel manufacturing methodology using the roll‐to‐roll process to enable continuous manufacturing of reentrant structures over large areas on a polymeric film was demonstrated. A two‐stage process, composed of embossing followed by post‐compression, allowed the fabrication of reentrant structures, which cannot be easily fabricated using other processes over large areas in a continuous manner. The treatment of the reentrant surface structures with an additional coating of 1 H, 1 H, 2 H, 2 H ‐perfluorooctyltrichlorosilane layer provided liquid repellency with contact angles of 155 and 140°, respectively, for water (Ylv  = 72 mN m −1 ) and diiodomethane (Ylv  = 50 mN m −1 ). © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 46980. Abstract :